Uso do ionóforo Monensina sódica na alimentação de vacas F1 HolandêsZebu: avaliação do consumo, desempenho e produção de leite - Juliana Guimar?es Laguna (2011)
The objectives were to evaluate the use of two source of protein supplementation with or without monensin on feed intake, ruminal parameters, performance and milk production of F1 Holstein-Zebu cows. Cows (n=15) with 21 days on milk and producing 19, kg/day were distributed, in a 5X5 Latin squares with three cows per treatment. The treatments were: 1- feeding concentrate during and corn silage after milking tim (C.SM); 2- C.SM+ nitromineral (C.SMNM); 3- C.SM + nitroprotéico (C.SMNP); 4- C.SMNM + monensin (C.SMNM+MO) e 5- C.SMNP + monensin (C.SMNP+MO). The NM and NP supplements were add to de corn silage. The protein supplementation to the C.SM increased the DMI (P<0,05), but the dry matter digestibility only increased when NP was added to the C.SM (P<0,05). The addition of monensin didnt change the DMI and dry matter digestibility (P>0,05). The protein supplementation didnt change acetate and butyrate concentrations (P>0.05), The monensin administration increased the propionateconcentration in the C.SMNM+MO treatment (P<0.05). It observed a decrease in the propionate and butyrate concentrations (P<0,05) in the C.SMNP treatment. An increase in the N-NH3 concentration (P<0.05) was noted in the C.SMNM tre ment. The pH did not change between the treatments (P>0,05). The milk p oduction was greater in C.SMNP+MO (17.7kg/d) and in the C.SMNP (16.7 kg/d) treatments as related do C.SM(14.9 kg/d) (P<0,05). The better efficiency on milk pr ion was observed on C.SM treatment than C.SMNM (P<0,05).